Development of a high-voltage laser triggered switch facility including initial optical and electrical diagnostics - Rose, Charles E., author; Yalin, Azer P., advisor; Menoni, Carmen S., committee member; Yourdkhani, Mostafa, committee member (Colorado State University. Libraries, 2019)
Pulsed power programs have been part of the United States strategic plan to address the nation's energy and defense needs since the 1960s. With escalating energy demand, one of the greatest challenges of our time is to develop clean and reliable energy sources with controlled fusion being an exciting and favorable candidate. Developing this technology has been an arduous and taxing effort with a breakthrough (supposedly) coming just around the corner for decades. Arguably, one of the leading testbeds for fusion research is Sandia National Laboratories (SNL) Z machine which is part of SNL's pulsed power program. The Z machine can create fusion-like conditions and allows the global research community to investigate pathways forward to a viable fusion reactor. Integral to developing future pulsed power technology and the next Z-pinch style machines, high voltage spark gap switches are an active research area and the focus of this thesis.

Partnering with SNL this body of work details our efforts to develop a high voltage laser triggered switch facility at Colorado State University (CSU). We present the design and development of the Pulsed Power and Plasma Science Center (P3SC) along with preliminary diagnostic measurements of a millimeter gap length optically accessible high-voltage laser triggered switch (HV-LTS). The current thrust of the P3SC laboratory is to investigate switch closure plasma characteristics associated with recently discovered gaps in the Tom Martin switch model which describes temporal plasma channel resistance of these HV-LTSs. Basic background and theory of the Martin model are discussed including laying out two key assumptions we believe are related to the error recently found. Specifically, radial switch closure plasma channel growth fits an Atk trend (A and K are constants), and constant electrical conductivity are assumed both spatially and temporally. Considering extremely high voltages and nanosecond timescales of switch closure, direct measurements of these characteristics are extremely difficult. Therefore, we present contact and non-contact optical measurements that can be utilized to help inform the assumptions laid out herein. Specifically, a current viewing resistor (CVR) that was designed to withstand peak energies involved during switch closure was used to directly measure voltage, and subsequent current, associated with switch closure. CVR measurements along with triggering data allowed for determination of essential electrical characteristics common for HV-LTS technology. With knowledge of these macroscopic electrical characteristics a non-contact optical measurement scheme was devised to investigate switch closure plasma's more closely, including schlieren imaging and optical emission spectroscopy (OES). Specifically, temporal mapping of the switch closure plasma channel through direct imaging allows for characterization of radial growth (first assumption), and OES can be used to calculate electron temperatures which can be related to the electrical conductivity (second assumption). Given this backdrop we present key electrical characteristics on an optically accessible HV-LTS including: self-break behavior, switch run time, jitter, and equivalent circuit resistance and inductance. Further, radial plasma growth is measured (from intensified camera images) and found to agree with the Martin model assumptions, albeit with variability yielding a potential error in calculated resistance of ~15%. OES of switch closure plasmas are also recorded and show the spectra to be dominated by continuum at early times with emission lines becoming visible at ~200 ns after a 25 kV shot and ~500 ns after a 50 kV shot. This data, to the best of the author's knowledge, represents the first publication of HV-LTS emission spectra. With this data we have shown that the electrical conductivity assumption is the most likely cause of the error found in the Martin model. Continued investigation is warranted, and a more robust optical measurement like Thomson scattering is being considered to inform the Martin model and more generally the next generation of pulsed power technology.
Keywords: laser triggered switch; plasma characterization; spectra; optical emission spectroscopy; high voltage switch; pulsed power